What's the catch? Archaeological application of rapid collagen-based species identification for Pacific Salmon. (April 2020) - Korzow Richter, Kristine; McGrath, Krista; Masson-MacLean, Edouard; Hickinbotham, Simon; Tedder, Andrew; Britton, Kate; Bottomley, Zoe; Dobney, Keith; Hulme-Beaman, Ardern; Zona, Margherita; Fischer, Roman; Collins, Matthew J.; et al.
Abstract: Pacific salmon ( Oncorhynchus spp.) are ecological and cultural keystone species along the Northwest Coast of North America and are ubiquitous in archaeological sites of the region. The inability to morphologically identify salmonid post-cranial remains to species, however, can limit our understanding of the ecological and cultural role different taxa played in the seasonal subsistence practices of Indigenous groups in the past. Here, we present a rapid, cost-effective ZooMS method to distinguish salmonid species based on collagen peptide mass-fingerprinting. Using modern reference material and an assemblage of 28 DNA-identified salmonid bones from the pre-contact Yup'ik site of Nunalleq, Western Alaska, we apply high-resolution mass spectrometry (LC-MS/MS) to identify a series of potential collagen peptide markers to distinguish Pacific salmon. We then confirm these peptide markers with a blind ZooMS analysis (MALDI-TOF-MS) of the archaeological remains. We successfully distinguish five species of anadromous salmon with this ZooMS approach, including one specimen that could not be identified through ancient DNA analysis. Our biomolecular identification of chum (43%), sockeye (21%), chinook (18%), coho (11%) and pink (7%), confirm the exploitation of all five available species of salmonid at Nunalleq. Highlights: We develop ZooMS to distinguish between Pacific Salmon species. We validate the method on an assemblage of 28 DNA-identified salmon bones. We demonstrate the use of all five available salmonid species at Nunalleq.